Medical management of Captured Persons. Issue 1 (14th October 2013) - Simpson, Robin G; Wilson, D; Tuck, J J
Abstract : In most conflicts there is the potential that there will be Captured Persons (CPERS) whose medical care is the responsibility of the capturing army. The standard of this care should be to the same standard as that afforded to one's own troops. However the medical practicalities of maintaining such standards can be difficult. This article reviews the practicalities of the medical care of CPERS as part of the UK deployment in Afghanistan on Operation HERRICK.